Understanding Mentor's Growth and Identity through Critical Self-Reflection Practice - Dewi Cahyaningrum; Drajati , Nur Arifah; Putri Handayani, Ellisa Indriyani; Tyarakanita, Agustina (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
Mentoring is a way of professional development for educators, teachers, and school leaders. This study aims to discover how mentors conceptualized the value of their practice and its impact on their growth and identity while guiding mentees in teacher-research mentoring activities. This study presents a case study of 4 English educators as mentors to gather a rich depiction of their mentoring phases. Understanding the mentors' pedagogy could help in understanding more about the process of their competence-building. Moreover, this process influences the process of their learning and impacts their identity. The data were obtained through critical self-reflection journals, mentoring conversations, and online focus group interviews. A model based on Mezirow's critical self-reflection practice is used to recognize mentors' growth and identity development. It suggested that three broad mentoring categories exist: self-focused, mentee-focused, and relationship-focused, which support them in achieving mentoring expertise. Moreover, mentors' motive is influenced by the identity development that occurs in the sociocultural environment, demonstrating their values, beliefs, and perspectives. This study's results also suggest that the mentoring program can be the basis for training, deploying expertise and competencies, and boosting personal and professional growth.